Perbedaan Motivasi dan Hasil Belajar Siswa yang Mengikuti Pembelajaran Secara Daring Dengan Siswa Yang Mengikuti Pembelajaran Secara Luring Pada Jurusan Otomatisasi Tata Kelola Perkantoran - Annisa Dildha Surya; Armida Armida (Universitas Negeri Padang, 2021)
This study aims to determine the difference between motivation and learning outcomes of students who take part in the learning process of students who take offline learning in the Office Management department at SMKN 1 Painan. This type of research was an experiment using a nonequievalent control group design. The population in this study were 72 students of SMKN 1 Painan. The analytical method used is the Wilcoxon Signed Rank Test (Z-test) and One Wat Sample Test using SPSS version 23, validity test and reliability test. The results showed that: (1) there was no difference in the learning motivation of students who participated in learning boldly with students who took offline learning in the Office of Automation in Office Management at SMKN 1 Painan and (2) there were differences in the learning outcomes of students who participated in learning boldly. with students who take offline learning in the Office of Automation Department of Management at SMKN 1 Painan. The difference in student learning outcomes is based on learning supporting factors that come from outside the students, namely the teacher and the learning media used. Meanwhile, students' learning motivation, both in bold learning and offline learning, both show attitudes and learning methods that have high motivation to participate in the learning that is being carried out. Based on the results of this study it is based on that to improve student learning outcomes in learning learning it is expected that students can develop a happy attitude to work independently by not cheating on classmates, develop attitudes to defend opinions by arguing theoretically, develop a happy attitude to solve problems) by Doing lots of practice questions without being ordered by the teacher, then developing an attitude of having hopes and aspirations for the future by showing seriousness in following class learning, and developing an attitude of obeying the rules by not making arrangements for the rules set by the teacher and the schoolKeywords : motivation, learning outcomes, online learning, offline learning